m6A Methylation Regulates Osteoblastic Differentiation and Bone Remodeling - Huang, Mei; Xu, Shaozhe; Liu, Lifei; Zhang, Miao; Guo, Jianmin; Yuan, Yu; Xu, Jiake; Chen, Xi; Zou, Jun (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis is a prevalent bone disease of the aging population, which is characterized by a decrease in bone mass because of the imbalance of bone metabolism. Although the prevention and treatment of osteoporosis have been explored by different researchers, there has not been a single anti-osteoporosis drug discovered. N6 methyladenosine (m6A) is a methylated adenosine nucleotide, which functions through its interaction with the proteins called "writers", "readers" and "erasers". The epigenetic regulation of m6A has been demonstrated to affect mRNA processing, nuclear export, translation, and splicing. At the cellular level, m6A modification has been known to affect cell proliferation, differentiation, and apoptosis of bone-related cells, such as bone marrow mesenchymal stem cells (BMSC), osteoblasts, and osteoclasts by regulating the expression of ALP, Runx2, Osterix, VEGF, and other related genes. Furthermore, PTH / Pth1r, PI3K‐Akt, Wnt/β‐Catenin, and other signaling pathways, which play important roles in the regulation of bone homeostasis, are also regulated by m6A. Thus, m6A modification may represent a potential target for osteoporosis treatment. The key roles of m6A modification in the regulation of bone health and osteoporosis are reviewed here in this article.